Unveiling interactive street art as narrative and playful elements in the city - Hassan, Hasyimah; Roslan, Nur Shazmiera Rosmidar; Zakariya, Khalilah (2015)
Interactive street art has emerged as a new form of public art that is starting to gain attention in different cities, including Malaysia. It is not simply just an artwork located along the streets, but it also brings a new kind of phenomenon to the city’s interactivity and vitality. As it is still considerably new in Malaysia, there has not been many local studies that examine interactive street art as a creative medium to enhance people’s experience. Based on case studies in Kuala Lumpur and Kuala Terengganu, this study analyses the potentials of interactive street art as narratives and playful elements in the city. Data is gathered through observation, mapping and conducting surveys among visitors that encounter the artwork. From the findings, this study identified how the artwork convey stories about the city, while also acting as informal playful elements. The recommendation explores other possibilities of designing interactive street art in the context of Malaysia.